ANALISIS KINERJA KUD SIALANG MAKMUR DI DESA SIALANG INDAH KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN - Masnilam '; Shorea Khaswarina; Ermi Tety (Indonesian Journal of Agricultural Economics, 2015)
The purpose of this study is to analyze the financial performance of KUD Sialang Makmur during the period 2008-2012. The results of the analysis of the financial performance obtained KUD Sialang Makmur seen from the level of liquidity by using the current ratio and quick ratio, KUD Sialang Makmur are in liquid state, means being able to meet its short term obligations because of the level of liquidity is above 100% because of the level of total current liabilities current assets. Level of solvency ratios, KUD Sialang Makmur is in a position solvable means the level of solvency in a good enough position that is 100% which means that if the KUD Sialang Makmur able to repay long-term debt, is due to the amount of assets is higher than the amount of debt. The level of activity ratio, KUD ability to obtain funds that are embedded in the assets is low to produce a number of revenue and net sales, KUD Sialang Makmur need to add capital to be invested in the assets to accelerate revenue generating assets and services net sales are also accepted by KUD Rates of return of KUD Sialang Makmur terms of economic profitability has declined, in terms of profitability of own capital gains KUD Sialang Makmur continue to increase and decline, means the net income used is higher than the net assets acquired cooperatives and use of inefficient costs issued by KUD Sialang Makmur indicated by the ratio of operating profits from the high that’s why is low.